Iatrogenic Carotid-Cavernous Fistula after Stent Assisted Coil Embolization of Posterior Communicating Artery Aneurysm - Park, Hye-Ran (J Cerebrovasc Endovasc Neurosurg, 2015)
Stent assisted coiling (SAC) is a useful technique for the treatment of wide necked complex aneurysm. As the frequency of SAC increases, stent-related complications such as thromboembolism, aneurysm rupture, and vessel rupture have been reported. However, to the best of our knowledge, carotid-cavernous fistula (CCF) after SAC has never been reported. The authors experienced a case of direct CCF after a SAC procedure for treatment of a complex posterior communicating artery (PCoA) aneurysm regrowth, which was treated by clip ligation 12 years before. The patient was managed conservatively and angiograms performed three months after the procedure showed the complete obliteration of the left PcoA aneurysm and the spontaneous disappearance of CCF. Navigation of Solitaire stent lumen with microcatheter can cause unexpected arterial injury, especially when the proximal tip is placed in the curved portion. It seems to be desirable to place the proximal tip of Solitaire stent in the straight portion whenever possible to reduce the risk of inadvertent arterial injury which might be caused by future navigation of stent lumen.